CONSUMER ACCEPTANCE OF POLISH BREAD PRODUCTS - Mańkowski, Dariusz R.; Fraś, Anna; Gołębiewska, Kinga; Gołębiewski, Damian (Plant Breeding and Seed Science, 2018)
Consumer acceptance of a variety of products, including bread is currently a very important economic and psychological criterion. Thus, understanding of consumer behaviour and preference should help bread manufacturers to satisfy the customers, particularly during launching new products. The study objective was to investigate preferences and expectations of Polish consumers concerning bread products as well as their comparison with manufacturers opinions. Surveys were collected using CATI method. Obtained results testified about clear differentiation of consumer requirements in relation to bread. It has been shown that preferences of bread consumers are connected with such factors as: sex, age, place of residence, employment, education and financial situation. Diverse demands of consumers result in a wide range of bread products on the market and a need for improving their quality and promotion of new brands.